2013
DOI: 10.1111/anu.12077
|View full text |Cite
|
Sign up to set email alerts
|

Response of fingerling stinging catfish,Heteropneustes fossilis(Bloch) to varying levels of dietaryl-leucine in relation to growth, feed conversion, protein utilization, leucine retention and blood parameters

Abstract: Growth response of fingerling Heteropneustes fossilis (6.8 AE 0.2 g; 11.2 AE 0.3 cm) to dietary L-leucine levels was assessed by conducting 8-week feeding trial in a flowthrough system (1-1.5 L min À1 ) at 28°C water temperature. Casein-gelatin-based isonitrogenous (380 g kg À1 ; crude protein) and isoenergetic [17.9 MJ kg À1 ; gross energy (GE)] basal diet was supplemented with different levels of L-leucine to achieve desired leucine levels ranging between 10 and 22.5 g kg À1 dry diet. Analysed values were 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 78 publications
6
9
0
Order By: Relevance
“…Whole body protein content of juvenile blunt snout bream was enhanced by increasing dietary leucine level up to 1.74%, which is in agreement with several other fish species such as rohu carp (Abidi and Khan, 2007) and stinging catfish (Farhat and Khan, 2014). In rats and humans, dietary leucine supplementation has been proven to acutely stimulate protein synthesis via activating TOR pathway which plays an important role in the limited step translation initiation (Li et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Whole body protein content of juvenile blunt snout bream was enhanced by increasing dietary leucine level up to 1.74%, which is in agreement with several other fish species such as rohu carp (Abidi and Khan, 2007) and stinging catfish (Farhat and Khan, 2014). In rats and humans, dietary leucine supplementation has been proven to acutely stimulate protein synthesis via activating TOR pathway which plays an important role in the limited step translation initiation (Li et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…The results indicated that leucine is an essential amino acid for blunt snout bream, and juvenile fish are able to utilize the crystalline L-leucine in the diet. Dietary leucine requirement for juvenile blunt snout bream was determined to be in the range of 1.44%-1.61% of diet (4.24%-4.74% of dietary protein) based on SGR and FER, which is similar to the values reported for grass carp (4.2% of dietary protein; Deng et al, 2014) and stinging catfish Heteropneustes fossilis (Bloch) (4.34% of dietary protein; Farhat and Khan, 2014), lower than the value reported for rainbow trout (9.2% of dietary protein; Choo et al, 1991), but higher than the values reported for Chinook salmon Oncorhynchus tshawytscha (3.9% of dietary protein; Chance et al, 1964), common carp Cyprinus carpio (3.3% of dietary protein; Nose, 1979) and channel catfish Ictalurus punctatus (3.5% of dietary protein; Wilson et al, 1980), mrigal carp Cirrhinus mrigala (3.9% of dietary protein; Ahmed and Khan, 2006) and rohu carp Labeo rohita (3.9% of dietary protein; Abidi and Khan, 2007). The variation for leucine requirement among fish species might be due to different fish species, 3.69 ± 0.09 c 3.50 ± 0.04 bc 3.15 ± 0.02 a 3.37 ± 0.09 a 3.23 ± 0.07 a 3.31 ± 0.10 ab 1 Means in the same rank sharing the same superscript letter are not significantly different determined by Tukey's test (P N 0.05).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In fingerling channel catfish (Ictalurus punctatus), weight gain significantly increased from 116% to 263% with increasing dietary leucine after an 8-week feeding trial (Wilson, Poe & Robinson, 1980). A similar change was found in fingerling stinging catfish (Heteropneustes fossilis), where a dietary leucine inclusion of 0.99%-1.74% resulted in an obvious increase in weight gain and feed efficiency of 163%-739% and 23.5%-51.3% respectively (Farhat & Khan, 2014). A similar change was found in fingerling stinging catfish (Heteropneustes fossilis), where a dietary leucine inclusion of 0.99%-1.74% resulted in an obvious increase in weight gain and feed efficiency of 163%-739% and 23.5%-51.3% respectively (Farhat & Khan, 2014).…”
supporting
confidence: 54%
“…Currently, threonine requirement studies are mostly focused on carps species including the Indian major carps (Nose ; Ravi & Devaraj ; Ahmed & Khan ; Abidi & Khan ). Although some of dietary essential amino acid requirements of this fish (Farhat & Khan 2012, ,b, ,b), including that on threonine requirement are available (Ahmed ), no information is yet available on dietary threonine level to optimize growth, feed conversion, protein utilization, threonine retention, nucleic acid indices and carcass quality of fingerling H. fossilis . Therefore, due to a number of reasons, as have been discussed under discussion section, a need has been felt to re‐evaluate optimum dietary threonine requirement of this fish.…”
Section: Introductionmentioning
confidence: 99%